Performance of the CREAM silicon charge detector during its first flight - J. Yang; H. S. Ahn; P. Allison; M. G. Bagliesi; J. J. Beatty; BIGONGIARI, GABRIELE; P. Boyle; J. T. Childers; N. B. Conklin; S. Coutu; M. A. DuVernois; O. Ganel; et al. (Tata Inst Fundamental Research, 2005)
The Cosmic Ray Energetics And Mass (CREAM) experiment was launched as a long duration balloon payload from McMurdo Station, Antarctica on 16 December 2004. For the charge measurement of incident cosmic-ray particles entering its calorimeter module, CREAM has a Silicon Charge Detector (SCD) comprised of 182 silicon sensors in an active area of 779mmx795mm. The sensors are DC-coupled PIN diodes fabricated from 380gm thick, n-type wafers. This presentation describes the construction of the detector and the performance of the SCD during its first flight.